An integrated optimisation model of reservoir and irrigation system applying uniform deficit irrigation. (2015) - Banihabib, Mohammad Ebrahim; Zahraei, Ali; Eslamian, Saeid
An optimisation model was derived for deficit irrigation to study four scenarios of water price-irrigation system combinations. The nonlinear objective function was optimised within a three-dimensional decision domain including: deficit irrigation ratios of wheat and tomato; and cropping area ratio of wheat to tomato. Four scenarios were employed regarding two pricing configurations including subsidised and non-subsided water prices and two irrigation systems as well. The results of the integrated optimisation model showed that the optimised deficit irrigation ratios are not changed by altering water price in each irrigation system. However, deficit irrigation of wheat crop increases net-benefit of farmers in subsidised price while, the net-benefit of farmers is not increased under the deficit irrigation of wheat crop with non-subsided water price and tomato crop in both price configurations. Sensitivity analysis of the model showed that annual tomato cropping costs and price are the most sensitive parameters in the optimisation.